Effect of Information System Quality on Administration via E-Office Applications: Evaluation of E-Office Performance at the KBB Manpower Office - Difta Ayu; Aldy Nurrohman; Athia Saelan; Fadhlanrashif Ibrahim Supriana (Journal of Information Systems and Technology Research, 2026)
The implementation of digital administrative systems in public sector institutions is expected to enhance efficiency, transparency, and accountability; however, partial system adoption and varying levels of user acceptance often limit their effectiveness. This study evaluates the implementation of a web-based E-Office application in public sector administration by examining how system quality, information quality, and service quality influence administrative management and employee acceptance. This research employs a descriptive qualitative approach by integrating the Information System Success Model and the Technology Acceptance Model (TAM). Qualitative data were collected through in-depth interviews with selected employees, direct observation of administrative workflows, and documentation analysis related to E-Office utilization in a local government institution. The findings indicate that system quality, information quality, and service quality positively contribute to administrative management effectiveness by accelerating document processing, improving information accessibility, and strengthening administrative accountability. In addition, perceived usefulness and perceived ease of use significantly influence employee acceptance of the E-Office application. Nevertheless, several challenges remain, including an outdated user interface, limited document search functionality, and the coexistence of manual and digital administrative processes. The novelty of this study lies in its qualitative integration of information system quality dimensions and the Technology Acceptance Model within a local government administrative context, providing empirical insights into both technical system performance and user acceptance to support public sector digital transformation.